CSF and serum ferritin levels in narcolepsy type 1 comorbid with restless legs syndrome. Issue 6 (20th May 2020) - Barateau, Lucie; Chenini, Sofiene; Lotierzo, Manuela; Rassu, Anna Laura; Evangelista, Elisa; Lopez, Régis; Gorce Dupuy, Anne‐Marie; Jaussent, Isabelle; Dauvilliers, Yves
Abstract: Objectives: To investigate whether cerebrospinal fluid (CSF) and serum ferritin levels differ between patients with narcolepsy type 1 (NT1) comorbid with restless legs syndrome (RLS) or periodic leg movements during sleep (PLMS), and patients with NT1 or controls without comorbid RLS or PLMS. Methods: Sixty‐six drug‐free patients with NT1 (44 males, age 38.5 years [14–81]) were enrolled, including 20 with RLS, 18 with PLMS index ≥15/h (six with both RLS and PLMS). Thirty‐eight drug‐free patients (12 males, age 22.5 years [12–61]) referred for sleepiness complaint, but without central hypersomnia, RLS, PLMS were included as controls. Clinical, electrophysiological and biological (CSF/serum ferritin, orexin [ORX]) data were quantified. Results: NT1 patients with and without RLS did not differ for age, gender, and body mass index (BMI). No between‐group differences were found for CSF ferritin, ORX, and serum ferritin levels. No CSF ferritin, ORX, and serum ferritin level differences were found between NT1 patients with and without PLMS, or with RLS or PLMS versus not. CSF‐ferritin levels were not different between NT1 and controls in adjusted analyses. CSF‐ferritin levels in the whole population correlated positively with age, serum‐ferritin, BMI, negatively with ORX, but not with PLMS index. In NT1, CSF‐ferritin levels correlated with age and serum‐ferritin but not with PLMS. Conclusion: The absence of CSF ferritin deficiency in NT1 with comorbid RLS or PLMS indicates normal brain iron levels in that condition. This result suggests that the frequent association between RLS, PLMS, and NT1 is not based on alterations in brain iron metabolism, a pathophysiological mechanism involved in primary RLS.